Urbanisation, nutrition transition and cardiometabolic risk: the Benin study - Delisle, H.; Ntandou-Bouzitou, Gervais D.; Agueh, V.; Sodjinou, R.; Fayom, B. (Cambridge University Press, 2012)
A rising prevalence of CVD and diabetes has been observed in sub-Saharan Africa, particularly in cities. The aim of the present study conducted in Benin was to examine the mediating role of nutrition transition in the relationship of urbanisation level and socio-economic status (SES) to cardiometabolic risk markers. A total of 541 subjects in apparent good health were randomly selected from the main city of Cotonou, a small town and its surrounding rural areas. SES was assessed based on a proxy for income and on education. Dietary intake and physical activity were assessed with at least two non-consecutive 24 h recalls. Scores for micronutrient adequacy and preventive diet were used as indicators of diet quality. Cardiometabolic risk markers were BMI, waist circumference (WC), blood pressure, serum cholesterol and insulin resistance according to homeostasis model assessment. A more advanced stage of nutrition transition, which correlated with lower diet quality scores and less physical activity, was observed in the large city compared with less urbanised locations. More obesity and more adverse cholesterol profiles, but also lower blood pressure, were present in the large city. Urbanisation, income, sedentary lifestyle and alcohol consumption, but not diet quality, independently contributed to higher BMI and WC. Higher micronutrient adequacy was independently associated with a better cholesterol profile. The study confirmed the positive rural–urban gradient in nutrition transition and cardiometabolic risk, except for blood pressure. This risk could be mitigated by a more adequate diet, particularly micronutrient intake, and a more active lifestyle.